The Effect of Media Technology, Motivation, and Initial Ability on Economic Learning Outcomes - Nurlina, Nurlina; Devilla, Rego; Burhanuddin, Rahmawati; Elpisah, Elpisah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
This research is classified as a descriptive quantitative research. The purpose of this study is to: (1) Explain the Influence of Technology Media on Learning Outcomes (2) explain the influence of Learning Motivation on Learning Outcomes (3) Explain the Influence of Initial Abilities on Learning Outcomes. (4) The Influence of the Use of Technology Media, Data collection using questionnaires, documentation and observation. This research method uses quantitative research, the instruments used are questionnaires and documentation. The results of the research that has been carried out state that partially (1) Technology Media Style has a positive effect on Learning Outcomes partially. (2) Learning Motivation has a positive effect on Learning Outcomes partially. (3) Students' Initial Ability has a positive effect on Learning Outcomes partially. (4) Technology Media, Learning Motivation and Students' Initial Ability have a simultaneous effect on Students' Learning Outcomes.